Transportation behaviours of the growing Canadian single-person households. (July 2017) - Young, Mischa; Lachapelle, Ugo
Abstract: Single-person households have been on the rise in Canada and especially in large Canadian cities. This demographic trend has many impacts on society, as in many regards solos behave differently than other strata's of the population. The objective of this paper is to explore the transport-related implications of the growth in single-person households in Canadian cities. The 2010 Canadian General Social Survey (N=15, 390) provides individual level socio demographic characteristics and time use diary that are used to classify individual's living situation (living alone, roommates, single parents, couples, and families) and to asses six transportation behaviours (owning a driver's license, access to a vehicle, commute distance, travel time by mode, overall trip frequency and trip frequency by purposes). Logistic, ordered logistic and negative binomial regressions are used to uncover the relationships between household types and travel behaviours, and to determine the transport-related implications of single-person households beyond other socio demographic characteristics in Canadian cities. Our findings confirm associations between single-person households and transportation behaviours and suggest they adopt a more environmentally sustainable lifestyle, at least with respect to travel. On average, single-person households commute shorter distances and are less likely to own a driver's license or have access to a vehicle than respondents from family households. The share of solos using a car is 17 percentage points lower than respondents living in family households and rates of use of active modes are 9 percentage points higher than respondents in couple households. Despite solos' overall trip frequency not significantly differing from family households, solos do partake in more food and social related trips. Age group difference exists within the solos category. The growth of single-person households may have considerable implications on urban transportation demand. If solos do chose to locate in places where alternative transportation modes are not accessible, the growth of this group may result in an increase in overall motorization rates because they are less likely to share a car. Highlights: Explores travel-related implications of growth in single-person households in Canada. Six travel behaviours are assessed with respect to six types of living situation. Travel-wise, single-person households adopt a more environmentally sustainable lifestyle. Solos tend to locate in places where alternative transportation modes are accessible. Growth of solos may result in an increase in overall motorization rates if they don't.